Empowering creativity: Exploring teacher agency in creative arts education - Hamza Alhassan; Fred Kyeremeh; Mohammed Issah Seini (CV. Yudhistt Fateeh, 2026)
This study examines the vital role of teacher agency in creative arts education, focusing on how autonomy, identity, and reflective practice contribute to pedagogical innovation. In creative disciplines, agency enables educators to build expressive, student-centred learning environments, even when constrained by rigid curricula, time limitations, and limited institutional support. Drawing on global literature, the paper highlights how teachers navigate these challenges by designing adaptable curricula, co-creating knowledge with students, and integrating culturally relevant, experimental methods. Emerging trends in the field are also explored, including transdisciplinary approaches that bridge the arts with science, humanities, and social justice. Arts-based professional development is emphasized as a means to foster long-term creative growth, alongside a growing awareness of the role of AI in education. While digital tools offer potential to enhance creativity, their impact on teacher voice and autonomy depends greatly on how they are implemented. Using a quantitative descriptive survey design, data were gathered from 387 creative arts educators to understand their perceptions of agency in areas such as curriculum adaptability, instructional decision-making, and institutional participation. The findings reveal that teacher agency is supported by ongoing reflection, collaboration, and active engagement with aesthetic practices, though it remains uneven across institutional levels. The study contributes to policy and professional development discourse by advocating for reforms that centre teacher voice, creativity, and well-being. It calls for systemic support structures that empower educators not only in the classroom but within broader educational decision-making processes.